ENDOMARKETING EM INSTITUIÇÕES DE ENSINO SUPERIOR: UM ESTUDO NA UNIVERSIDADE FEDERAL DO PAMPA - Mikaela Daiane Prestes Floriano; Andressa Hennig Silva (Revista Gestão Universitária na América Latina, 2018)
The importance of actions aimed at satisfying the demands of internal clients of organizations is increasingly evident in view of the need to develop a pleasant working environment for workers. In view of this, this article sought to verify how the servers evaluate the actions of endomarketing performed at a Federal University located in the south of the state of Rio Grande do Sul. For this purpose, a Survey was conducted, of a descriptive nature and a quantitative and qualitative approach. The data collection took place from the application of a questionnaire to the servers of the university. The results point out that the endomarketing has been little propagated in the institution, evidencing the indispensability of immediate improvement of some aspects of the four dimensions of the endomarketing of Inkotte (2000).